Proteomic Response of Rat Pituitary Under Chronic Mild Stress Reveals Insights Into Vulnerability and Resistance to Anxiety or Depression - Tian, Fenfang; Liu, Dan; Chen, Jin; Liao, Wei; Gong, Weibo; Huang, Rongzhong; Xie, Liang; Yi, Faping; Zhou, Jian (Frontiers in Genetics, 2021)
Chronic stress as one of the most significant risk factor can trigger overactivity of hypothalamic-pituitary-adrenal (HPA) axis in depression as well as anxiety. Yet, the shared and unique neurobiological underpinnings underlying the pituitary abnormality in these two disorders have not been made clear. We previously have established depression-susceptible, anxiety-susceptible and insusceptible groups using a valid chronic mild stress (CMS) model. In this work, the possible protein expression changes in the rat pituitary of these three groups were continuously investigated through the use of the comparative quantitative proteomics and bioinformatics approaches. The pituitary-proteome analysis identified totally 197 differential proteins as a CMS response. These deregulated proteins were involved in diverse biological functions and significant pathways potentially connected with the three different behavioral phenotypes, likely serving as new investigative protein targets. Afterwards, parallel reaction monitoring-based independent analysis found out that expression alterations in Oxct1, Sec24c, Ppp1cb, Dock1, and Coq3; Lama1, Glb1, Gapdh, Sccpdh, and Renbp; Sephs1, Nup188, Spp1, Prodh1, and Srm were specifically linked to depression-susceptible, anxiety-susceptible and insusceptible groups, respectively, suggesting that the same CMS had different impacts on the pituitary protein regulatory system. Collectively, the current proteomics research elucidated an important molecular basis and furnished new valuable insights into neurochemical commonalities and specificities of the pituitary dysfunctional mechanisms in HPA axis underlying vulnerability and resistance to stress-induced anxiety or depression.